Gonorrhoea: New Threats from Multidrug-Resistant Strains of Neisseria Gonorrhoeae, and the Epidemiological Situation - Młynarczyk-Bonikowska, Beata; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2025)
Europe and Poland are reporting increasing gonorrhea rates. This article outlines the key challenges in diagnosing drug‑resistant Neisseria gonorrhoeae, tracking their spread, and understanding resistance mechanisms, along with an overview of new therapeutic options. Real‑time PCR remains the primary diagnostic method, while culture is essential for antibiotic susceptibility testing. Transporting viable bacteria is difficult due to their high sensitivity to external conditions. The discussion includes resistance mechanisms to oxy‑imino‑cephalosporins, penicillins, azithromycin, ciprofloxacin, tetracyclines, and spectinomycin. Emerging drugs offer potential solutions to resistant strains. Notable candidates include gepotidacin, zoliflodacin, solithromycin, sitafloxacin, and delafloxacin. Genotyping supports the surveillance of individual strains, particularly multidrug‑resistant ones. Relevant methods include whole genome sequencing (WGS), multi‑antigen sequence typing (NG‑MAST), multilocus sequence typing (MLST), core genome multilocus sequence typing (cgMLST), and Neisseria gonorrhoeae Sequence Typing for Antimicrobial Resistance (NG‑STAR).